FGF21 alleviates acute liver injury by inducing the SIRT1‐autophagy signalling pathway. Issue 3 (4th January 2022) - Yang, Xiaoning; Jin, Zhongqian; Lin, Danfeng; Shen, Tianzhu; Zhang, Jiangnan; Li, Dan; Wang, Xuye; Zhang, Chi; Lin, Zhuofeng; Li, Xiaokun; Gong, Fanghua
Abstract: Liver injury can lead to different hepatic diseases, which are the mainly causes of high global mortality and morbidity. Autophagy and Sirtuin type 1 (SIRT1) have been shown protective effects in response to liver injury. Previous studies have showed that Fibroblast growth factor 21 (FGF21) could alleviate acute liver injury (ALI), but the mechanism remains unclear. Here, we verified the relationship among FGF21, autophagy and SIRT1 in carbon tetrachloride (CCl4 )‐induced ALI. We established CCl4 ‐induced ALI models in C57BL/6 mice and the L02 cell line. The results showed that FGF21 was robustly induced in response to stress during the development of ALI. After exogenous FGF21 treatment in ALI models, liver damage in ALI mice was significantly reduced, as well as serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels. Consistently, FGF21 also greatly reduced the levels of ALT, AST, pro‐inflammatory cytokines interleukin 6 (IL6) and tumour necrosis factor‐alpha (TNFα) in ALI cell lines. Mechanistically, exogenous FGF21 treatment efficiently upregulated the expression of autophagy marker microtubule‐associated protein light chain‐3 beta (LC3 II) and autophagy key molecule coiled‐coil myosin‐like BCL2‐interacting protein (Beclin1), which was accompanied by alleviating hepatotoxicity in CCl4 ‐treated wild‐type mice. Then, we examined how FGF21 induced autophagy expression and found that SIRT1 was also upregulated by FGF21 treatment. To further verify our results, we constructed an anti‐SIRT1 lentit‐RNAi to inhibit SIRT1 expression in mice and L02 cells, which reversed the protective effect of FGF21 on ALI. In summary, these results indicate that FGF21 alleviates ALI by enhancing SIRT1‐mediated autophagy.